Guardians of contested borders. Transnational Strategies for Coptic Survival - Galal, Lise Paulsen (Kvinder, Køn & Forskning, 2007)
Coptic interpretations of the status of Copts in Egypt affect their trans-national strategies and their gender constructs embedded in their minority discourses. In particular, different Coptic transnational organisations and their negotiations of Coptic identity are influential.